Accelerating adolescent HIV research in low-income and middle-income countries: evidence from a research consortium. (1st December 2021) - Tucker, Joseph D.; Iwelunmor, Juliet; Abrams, Elaine; Donenberg, Geri; Wilson, Erin C.; Blachman-Demner, Dara; Laimon, Lauren; Taiwo, Babafemi O.; Kuhns, Lisa M.; John-Stewart, Grace C.; Kohler, Pamela; Subramanian, Sujha; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Many adolescents and young adults (AYA) have unmet HIV prevention needs. We describe the Prevention and Treatment through a Comprehensive Care Continuum for HIV-affected Adolescents in Resource Constrained Settings (PATC 3 H) consortium organization, transition milestones, and youth engagement strategies. The PATC 3 H consortium focuses on reducing HIV incidence and related health disparities among AYA. Design and Methods: Organizational data were obtained from the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) and supplemented with a brief survey completed by study principal investigators. Transition from the initial phase (years 1 and 2) to the subsequent phase (years 3 and 5) was contingent on meeting prespecified milestones. We reviewed the structure and function of the research consortium, identified shared elements of transition milestones, and examined common youth engagement strategies. Results: The PATC 3 H consortium supports eight research studies through a milestone transition mechanism. The consortium includes AYA HIV research studies in seven countries – Brazil, Kenya, Mozambique, Nigeria, South Africa, Uganda, and Zambia. The NIH request for applications required transition milestones that included early consultation with stakeholders. The transition milestones required by NIH for the eight studies included early consultation with health and policy stakeholders, pilot intervention data, and commitment from national government stakeholders. All studies provided multiple pathways for AYA engagement, including AYA advisory boards and youth-led research studies. Conclusion: Data suggest that requiring milestones to transition to the final phase may have facilitated health and policy stakeholder engagement and enhanced formative assessment of regulatory protocols. These data have implications for designing engaged research studies in low and middle-income countries.